Preparation of the endometrium for frozen embryo transfer: an update on clinical practices - Yiting Zhang; Xiao Fu; Shuli Gao; Shuzhe Gao; Shanshan Gao; Jinlong Ma; Zi-Jiang Chen (BMC, 2023)
Abstract Over the past decade, the application of frozen-thawed embryo transfer treatment cycles has increased substantially. Hormone replacement therapy and the natural cycle are two popular methods for preparing the endometrium. Hormone replacement therapy is now used at the discretion of the doctors because it is easy to coordinate the timing of embryo thawing and transfer with the schedules of the in-vitro fertilization lab, the treating doctors, and the patient. However, current results suggest that establishing a pregnancy in the absence of a corpus luteum as a result of anovulation may pose significant maternal and fetal risks. Therefore, a 'back to nature' approach that advocates an expanded use of natural cycle FET in ovulatory women has been suggested. Currently, there is increasing interest in how the method of endometrial preparation may influence frozen embryo transfer outcomes specifically, especially when it comes to details such as different types of ovulation monitoring and different luteal support in natural cycles, and the ideal exogenous hormone administration route as well as the endocrine monitoring in hormone replacement cycles. In addition to improving implantation rates and ensuring the safety of the fetus, addressing these points will allow for individualized endometrial preparation, also as few cycles as possible would be canceled.